A study of altered cytokine rhythms associated with successful implantation in cows. Issue 2 (4th March 2018) - Manjari, P.; Kapoor, Suresh; Hyder, Iqbal; De, S.; Mohanty, A. K.; Dang, A. K.
Abstract: Implantation is a critical process wherein the dam accepts the semi-allogenic embryo, characterized by certain vital immunological changes involving certain factors and cytokines. The current study was undertaken in Sahiwal cows to analyze the changes in certain selective immunological components of the body during peri-implantation period. Post-insemination the study was performed for a period till day 40 and the plasma was used to estimate the levels of progesterone, interleukin 1β (IL-1β), IL-2, IL-4, IL-6, and leukemia inhibiting factor (LIF) using Bovine specific ELISA Test Kits. The phagocytic activity and mRNA expression of progesterone-induced blocking factor (PIBF) were also analyzed. It was observed that in pregnant cows, the expression of PIBF increased from day 16th onward and remained high throughout the study period whereas the phagocytic activity was higher in non-pregnant cows all through the study period. The IL-1β, IL-2, and IL-6 were significantly higher in non-pregnant cows from 16th to 18th day post-AI as compared to P cows. On the other hand, IL-4 and LIF showed a significantly higher concentration in pregnant cows during peri-implantation period. Hence, it can be concluded that early embryonic survival is dependent on interplay of certain critical immunological factors in the body.